Neuroticism-related personality traits are associated with posttraumatic stress after abortion: findings from a Swedish multi-center cohort study - Inger Wallin Lundell; Inger Sundström Poromaa; Lisa Ekselius; Susanne Georgsson; Örjan Frans; Lotti Helström; Ulf Högberg; Agneta Skoog Svanberg (BMC, 2017)
Abstract Background Most women who choose to terminate a pregnancy cope well following an abortion, although some women experience severe psychological distress. The general interpretation in the field is that the most consistent predictor of mental disorders after induced abortion is the mental health issues that women present with prior to the abortion. We have previously demonstrated that few women develop posttraumatic stress disorder (PTSD) or posttraumatic stress symptoms (PTSS) after induced abortion. Neuroticism is one predictor of importance for PTSD, and may thus be relevant as a risk factor for the development of PTSD or PTSS after abortion. We therefore compared Neuroticism-related personality trait scores of women who developed PTSD or PTSS after abortion to those of women with no evidence of PTSD or PTSS before or after the abortion. Methods A Swedish multi-center cohort study including six Obstetrics and Gynecology Departments, where 1294 abortion-seeking women were included. The Screen Questionnaire-Posttraumatic Stress Disorder (SQ-PTSD) was used to evaluate PTSD and PTSS. Measurements were made at the first visit and at three and six month after the abortion. The Swedish universities Scales of Personality (SSP) was used for assessment of Neuroticism-related personality traits. Multiple logistic regression analyses were performed to investigate the risk factors for development of PTSD or PTSS post abortion. Results Women who developed PTSD or PTSS after the abortion had higher scores than the comparison group on several of the personality traits associated with Neuroticism, specifically Somatic Trait Anxiety, Psychic Trait Anxiety, Stress Susceptibility and Embitterment. Women who reported high, or very high, scores on Neuroticism had adjusted odds ratios for PTSD/PTSS development of 2.6 (CI 95% 1.2-5.6) and 2.9 (CI 95% 1.3-6.6), respectively. Conclusion High scores on Neuroticism-related personality traits influence the risk of PTSD or PTSS post abortion. This finding supports the argument that the most consistent predictor of mental disorders after abortion is pre-existing mental health status.